Self-assembled growth of GaN nanowires on amorphous AlxOy: from nucleation to the formation of dense nanowire ensembles. (29th June 2016) - Sobanska, M; Fernández-Garrido, S; Zytkiewicz, Z R; Tchutchulashvili, G; Gieraltowska, S; Brandt, O; Geelhaar, L
Abstract: We present a comprehensive description of the self-assembled nucleation and growth of GaN nanowires (NWs) by plasma-assisted molecular beam epitaxy on amorphous Al x O y buffers (a-Al x O y ) prepared by atomic layer deposition. The results are compared with those obtained on nitridated Si(111). Using line-of-sight quadrupole mass spectrometry, we analyze in situ the incorporation of Ga starting from the incubation and nucleation stages till the formation of the final nanowire ensemble and observe qualitatively the same time dependence for the two types of substrates. However, on a-Al x O y the incubation time is shorter and the nucleation faster than on nitridated Si. Moreover, on a-Al x O y we observe a novel effect of decrease in incorporated Ga flux for long growth durations which we explain by coalescence of NWs leading to reduction of the GaN surface area where Ga may reside. Dedicated samples are used to analyze the evolution of surface morphology. In particular, no GaN nuclei are detected when growth is interrupted during the incubation stage. Moreover, for a-Al x O y, the same shape transition from spherical cap-shaped GaN crystallites to the NW-like geometry is found as it is known for nitridated Si. However, while the critical radius for this transition is only slightly larger for a-Al x O y than for nitridated Si, the critical height is more than six times larger for a-Al x O y . Finally, we observe that in fully developed NW ensembles, the substrate no longer influences growth kinetics and the same N-limited axial growth rate is measured on both substrates. We conclude that the same nucleation and growth processes take place on a-Al x O y as on nitridated Si and that these processes are of a general nature. Quantitatively, nucleation proceeds somewhat differently, which indicates the influence of the substrate, but once shadowing limits growth processes to the upper part of the NW ensemble, they are not affected anymore by the type of substrate.